Real-Time Implementation of an Internet of Things-Based Rose Eco-Enzyme Fermentation Monitoring System for Women Farmers Group (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The surplus of rose flower harvest in Ngliman Village causes some rose petals to be underutilized and potentially become organic waste. One effort to utilize this is through eco-enzyme fermentation using rose petals. However, the fermentation process carried out by the Women Farmers Group (KWT) is still monitored manually, making fermentation conditions difficult to control and at risk of failure. This study aims to implement an Internet of Things (IoT)-based eco-enzyme fermentation monitoring system to monitor fermentation conditions in real time. The research methods used include the design, development, and implementation of a monitoring system using an ESP32 microcontroller, a DHT22 sensor to measure temperature, and an MPX Pressure sensor to measure gas pressure during the fermentation process. The obtained data is sent via the internet and displayed on a web-based dashboard. The results show that the system is able to read, send, and display temperature and gas pressure data in real time effectively throughout the fermentation process. The developed system helps users monitor fermentation conditions more effectively, improves the accuracy of process monitoring, and reduces the risk of fermentation failure. Thus, this IoT-based monitoring system has the potential to support the optimization of rose petal waste processing into useful eco-enzyme products